Vitality as an alternative to safety in Urban Public Spaces: the case of Palmira-Colombia - Cárdenas-O´Byrne, Sabina (Prospectiva. Revista de Trabajo Social e Intervención Social, 2016)
This article is the result of a study in Palmira city, in the Department of Valle that measures the correlation between attitude of people toward safety and vitality of public spaces, using the Vital City model proposed by architecture. This model is an alternative to the fortified model that promotes enclosure as the only way out for keeping safety in public spaces. These findings seek to incorporate safety to city renewal processes throughout the sustainable perspective offered by Vital City, and to build a baseline that may allow in the future to measure the impact of these renovations in terms of safety. Non-intrusive observation was mainly used to prove the hypothesis that places with higher vitality foster better attitudes towards safety. Therefore, typology in culs-de-sacs; density of people in space; cleanness and maintenance; usage of transitional spaces; visibility in borders; and absence of physical barriers, as well as lowering the amount of police patrols in the area, have proven to be the environmental cues that most improve the attitude toward safety in Palmira´s public spaces.